A Detailed Analysis of the Association between Urate Deposition and Erosions and Osteophytes in Gout. Issue 10 (21st September 2020) - Pecherstorfer, Caroline; Simon, David; Unbehend, Sara; Ellmann, Hanna; Englbrecht, Matthias; Hartmann, Fabian; Figueiredo, Camille; Hueber, Axel; Haschka, Judith; Kocijan, Roland; Kleyer, Arnd; Schett, Georg; et al.
Abstract : Objective: To characterize in detail the structural bone changes associated with the deposition of monosodium urate crystals in the first metatarsophalangeal (MTP1) joint in patients with tophaceous gout. Methods: Twenty patients with tophaceous gout and involvement of the MTP1 joint received both dual‐energy computed tomography (DECT) of the feet for the detection of tophi and high‐resolution peripheral quantitative computed tomography (HR‐pQCT) of the feet for the detection of bone erosions and osteophytes. Demographic and clinical data were collected. Tophi in DECT and erosions and osteophytes in HR‐pQCT were overlayed to define their anatomical relation. In addition, the feet of 20 sex‐ and age‐matched healthy controls were scanned to define the normal architecture of the MTP1 joint. Results: Patients with gout had an increased number and extent of bone erosions and osteophytes compared with their healthy counterparts (erosions: 5 [0‐17] vs 1 [1‐2], 45.32 mm 3 [7.26‐550.32] vs 0.82 mm 3 [0.15‐21.8]; osteophytes: 10.5 [0‐26] vs 1 [0‐10], 4.93 mm [0.77‐7.19 mm] vs 0.93 mm [0.05‐7.61 mm]; all P < 0.001). The median tophi volume detected by DECT (0.12 mm 3 [0.01‐2.53]) was highly associated with the total volume of erosions ( r = 0.597, P = 0.005). Conclusion: Gout patients show increased changes in their bone microarchitecture. The extent of uric acid deposition is positively correlated with the extent of bone loss at the MTP1 joint, highlighting the strong cohesion of inflammation and erosive changes.